EVALUATION OF ELDERLY PATIENTS WITH COLORECTAL PATHOLOGY - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
To evaluate how older age and comorbidities affect outcomes in patients undergoing surgery for colorectal pathology ( hemorrhoids , anal fissure, fistula ), especially considering the impact of age, gender, and comorbidities on length of hospital stay, readmission rates, reoperation rates, and overall health and survival. The study aimed to identify risk factors for adverse outcomes in elderly patients with colorectal pathology and to provide information on appropriate perioperative management strategies to improve postoperative outcomes in this population. Methods: Therefore, this study aimed to evaluate how older age and comorbidities affect outcomes in patients undergoing surgery for colorectal pathology (KRP ) at the Samarkand State Medical University, multidisciplinary clinic-1. This retrospective cohort study included patients aged 40 years and older who underwent elective or emergency surgery in the colorectal region between January 2022 and December 2023. The study analyzed independent variables such as age, gender, and comorbidities, as well as variables related to the surgical procedure such as stoma creation, hospitalization history, surgical approach, American Society of Anesthesiologists (ASA) score, and Charlson Comorbidity Index score . A total of 96 patients with CR P underwent surgical resection. Patient age had a significant effect on both pre- and post-resection length of stay (LOS) and overall survival (OS), but not on 30-day readmission and reoperation rates. Multivariate analysis showed that age was a risk factor for longer preoperative and postoperative LOS and 30-day and 365-day mortality, but was not associated with an increased risk of 30-day reoperation and readmission. Results: The study also found that chronic heart failure increased the risk of 30-day mortality by fourfold, preoperative survival by 51% and postoperative survival by 33%, while chronic kidney failure was associated with a 74% increase in 30-day readmissions. Conclusion: These findings suggest that advanced age and comorbidities require careful preoperative assessment and appropriate perioperative management to improve surgical outcomes in elderly patients undergoing elective or emergency resection of colorectal cancer. These findings have important implications for clinicians and health care providers managing elderly patients with CRC